2019
DOI: 10.1088/1741-4326/ab430d
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of tokamak boundary plasma turbulence transport in setting the divertor heat flux width

Abstract: The BOUT  +  + code has been used to simulate edge plasma electromagnetic (EM) turbulence and transport, and to study the role of EM turbulence in setting the scrape-off layer (SOL) heat flux width λq. More than a dozen tokamak discharges from C-Mod, DIII-D, EAST, ITER and CFETR have been simulated with encouraging success. The parallel electron heat fluxes onto the target from the BOUT  +  + simulations of C-Mod, DIII-D, and EAST follow the experimental heat flux width scaling of the inverse dependence on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 48 publications
4
78
0
Order By: Relevance
“…2017; Xu et al. 2019) predicts considerably wider heat flux widths in low- plasmas. For this reason, data from SPARC on the divertor heat flux width scaling will be an important physics result and may help resolve the differences between empirical scaling and modelling predictions.…”
Section: Investigation Of Sparc Physicsmentioning
confidence: 97%
See 1 more Smart Citation
“…2017; Xu et al. 2019) predicts considerably wider heat flux widths in low- plasmas. For this reason, data from SPARC on the divertor heat flux width scaling will be an important physics result and may help resolve the differences between empirical scaling and modelling predictions.…”
Section: Investigation Of Sparc Physicsmentioning
confidence: 97%
“…Since the ability to balance a perfect double-null is uncertain, the SPARC divertors are being conservatively designed to operate in single-null. SPARC operation will represent an extrapolation in the empirical parallel heat flux width scaling (λ q ≈ 0.2 mm, with peak unmitigated parallel heat fluxes estimated to be of the order of 10 GW m −2 ) (Eich et al 2013;Brunner et al 2018) and some recent modelling (Chang et al 2017;Xu et al 2019) predicts considerably wider heat flux widths in low-ρ * plasmas. For this reason, data from SPARC on the divertor heat flux width scaling will be an important physics result and may help resolve the differences between empirical scaling and modelling predictions.…”
Section: Investigation Of Sparc Physicsmentioning
confidence: 99%
“…[12]. There is also a BOUT++ fluid turbulence simulation result [15] that shows broadening of λq in the 15MA Q = 10 ITER plasma. Since a fluid modeling does not contain the kinetic physics that are essential in the present work, such as the finite ion orbit width and trapped electron modes, we do not attempt to compare the present work with Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Since a fluid modeling does not contain the kinetic physics that are essential in the present work, such as the finite ion orbit width and trapped electron modes, we do not attempt to compare the present work with Ref. [15]. SOLPS-ITER modeling of the 15MA ITER discharge has shown that an anomalous electron thermal diffusivity of 1m 2 /s in the SOL can lead to a λq enhancement from Eich/Goldston formula prediction (≲ 1mm) to 3-4mm [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our initial analysis suggests that Landau fluid closure results in a nearly one order of magnitude weaker heat conduction comparing to the value given by the flux-limited model both in the closed flux region and in the SOL, as attested by the substantial diminishing amplitudes of ∇ q (red dotted lines) in Figure 7. However, the impact of the improved Landau fluid closure on edge instability, turbulence, transport and most importantly, divertor heat flux width [42] doesn't fit in the scope of this paper and will be left for a future study.…”
Section: Landau Fluid Closurementioning
confidence: 99%